Topology optimisation of offshore wind turbine jacket foundation for fatigue life and mass reduction - Marjan, Ali; Huang, Luofeng (Elsevier, 2023)
Offshore wind turbines are frequently regarded as a pricey source of electricity, and efforts are being made to lower both capital and operational costs by developing lighter and more robust structures. This paper presents a topology optimisation method to obtain a novel jacket foundation design by finding the optimum load path on the structure. The OC4 jacket model was computationally simulated considering the Aero-Hydro-Servo-Elastic loads, and the topology optimisation method was used to obtain a series of new designs. The structural optimisation is performed based on the dynamic response of the jacket, whilst restrained by relevant international design standards. In particular, time-domain fatigue simulations were performed to assess the structural integrity of the topology-optimised jacket for the first time. As a result, a range of optimised models with various thickness and diameter options are presented, which are shown to be rational and verify the optimisation procedure. The structural performance of the optimised geometry demonstrates the original jacket foundation is conservative, and the selection of optimised geometry achieved a mass reduction of 35.2% and simultaneously realised a 37.2% better fatigue life. The overall optimisation procedure and results provide useful practicalities for the design of offshore wind turbine foundations and potentially facilitate the structural integrity and cost reduction of the relevant industry.
Keywords: Topology optimisation; Offshore wind turbine; Jacket foundation; Aero-hydro-servo-elastic loads; Fatigue; Mass reduction